2022
DOI: 10.1155/2022/3955748
|View full text |Cite
|
Sign up to set email alerts
|

Decorin Protects Retinal Pigment Epithelium Cells from Oxidative Stress and Apoptosis via AMPK-mTOR-Regulated Autophagy

Abstract: Age-related macular degeneration (AMD) is the leading cause of irreversible visual loss among the elderly worldwide with unidentified pathogenesis and limited therapeutic options. Oxidative stress-induced damage to the retinal pigment epithelium (RPE) is central in the development and progression of AMD. Decorin (DCN), a small leucine-rich proteoglycan, possesses powerful antifibrotic, anti-inflammatory, and antiangiogenic properties. DCN has also been reported to serve a cytoprotective role in various cell ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It is well known that abnormal autophagy and apoptosis contribute to the development of AMD [ 38 , 39 ]. Our data showed that the dying cells displayed a large-scale accumulation of autophagosomes following NaIO 3 insult.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that abnormal autophagy and apoptosis contribute to the development of AMD [ 38 , 39 ]. Our data showed that the dying cells displayed a large-scale accumulation of autophagosomes following NaIO 3 insult.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, pharmacological manipulation of autophagic activity could be a therapeutic target for retinal damage-related disorders. Although autophagy in RPE cells exposed to oxidative stress, particularly H 2 O 2 , is known to contribute to apoptosis induction [ 49 ], RPE cells might also be protected from oxidative stress and apoptosis through promotion of autophagy [ 59 ]. In this study, H 2 O 2 -induced autophagy in ARPE-19 cells was blocked by 3-MA, an autophagosome blocker, suggesting that H 2 O 2 -mediated autophagy might contribute to apoptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“… 227 The beneficiary effect on “cellular protection” is also shown by the finding that decorin protects intestinal cells via its pro-autophagic action in inflammatory bowel disease 228 and seemingly protects retinal pigment epithelial cells from oxidative stress and apoptosis via AMPK-mTOR-regulated autophagy. 229 Moreover, decorin evokes reversible mitochondrial depolarization in carcinoma and vascular endothelial cells. 230 This pathway is novel and requires further elucidation; decorin-evoked mitophagy requires TCHP/mitostatin mRNA interaction with PGC-1α which results in accumulation of mitostatin.…”
Section: Proteoglycans and Heparanase As Proautophagic Secreted Factorsmentioning
confidence: 99%